Low- to Moderate-Level Forest Disturbance Effects on Plant Functional Traits and Associated Soil Microbial Diversity in Western Himalaya - Singh, Shipra (Frontiers in Forests and Global Change, 2021)
This study quantifies the effect of low- to moderate-intensity anthropogenic activities and natural activities affecting less than 40% of the canopy cover on major plant functional traits and associated soil microbial diversity in western Himalayan temperate forests. Plots of 0.1 ha were placed in the temperate forests along disturbance gradient and were categorized based on lopping intensity, deadwood counts, grazing, and litter removal. Plots were classified into three classes, i.e., low disturbance intensity (LDI) and moderate disturbance intensities (MDI1 and MDI2) based on lopping activities and canopy cover. The study was conducted on functional traits related to growth and survival strategies of a species in a complex forest ecosystem. Furthermore, DNA was extracted and metagenome of soil samples was performed using Illumina MiSeq platform from three disturbance classes to study the effect of disturbance and plant traits on microbial diversity. Tree basal area was found to be most significantly affected by disturbance intensity. Total density was found to be greater for the LDI site. Specific leaf area (SLA) and crown cover (CC) were the most affected traits in the moderately disturbed sites, whereas maximum plant height (HT) and seed mass (SM) were least affected by disturbance. Soil microbial diversity was found to be negatively associated with disturbance index. Microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) were found to be significantly higher in LDI sites. Disturbance level elicited variation in microbial community composition. Proteobacteria was the most abundant phylum and Phenylobacterium, DA101, and Candidatus solibacter were mainly abundant at the genus level. A decreasing level of disturbance due to the absence of human residences in the LDI site led to the dominance of Phenylobacterium (27%) which reduced to 18% in MDI1 site. Shannon alpha bacterial diversity and plant species diversity (H′) were found to be greatest for MDI2 site. In forests with varying levels of management, treefall gaps due to low levels of logging intensity might have a similar effect to those of reduced lopping intensities and deadwood count (due to natural disturbances) in the study sites. The study concludes that moderate disturbance is important for promoting species diversity and species richness (SR), but species having conservative ecological strategies would be more prone to continued disturbance intensity. Therefore, low- to moderate-level disturbance in such forests can be used as a model for natural treefall gaps, and moderate-level disturbance intensity plays a powerful role in buffering ecosystem processes.